A Trend Analysis on the Qualitative Research of Dental Hygiene in Korea (2000∼2023) - An-Na Yeo; Yang-Keum Han (The Korean Society of Dental Hygiene Science, 2024)
Background: This study aimed to analyze trends in qualitative research within the field of dental hygiene, focusing on papers published in Korean journals from 2000 to 2023. As dental hygienists play a crucial role in preventive oral health, understanding the breadth and depth of qualitative research in this field is essential for advancing practice and education. Methods: This descriptive survey research study analyzed 23 qualitative studies using the Consolidated Criteria for Reporting Qualitative Research (COREQ) as a framework. Studies were selected through a comprehensive search of Korean databases. The analysis covered research topics, participant types, methodological approaches, and adherence to COREQ domains, including "Research Team and Reflexivity," "Study Design," and "Analysis and Findings." Results: The analysis revealed that most studies employed a phenomenological methodology (36.4%). Additionally, 87.0% of the studies mentioned Institutional Review Board (IRB) approval and only 8.7% utilized qualitative data analysis software. The studies primarily focused on oral care for the elderly, communication, and the experiences of dental hygienists. Furthermore, 95.7% of the studies included participant quotations, but only 56.5% checked data saturation. Conclusion: This study highlights the need for a more diverse methodological approach in dental hygiene research. Journals should also emphasize strict adherence to IRB guidelines and encourage the use of qualitative data analysis software to enhance the rigor of research. By strengthening the systematic foundation of qualitative research in dental hygiene, the field can better address clinical challenges and expand the understanding of dental hygienists' work environments.